Towards an ethics of reading Muslims: encountering difference in Kamila Shamsie's Home Fire. Issue 7 (3rd July 2021) - Ahmed, Rehana
ABSTRACT: This article explores the ethics of reading across difference in a secular literary marketplace that is invested in representations of Muslims. Focusing on Kamila Shamsie's Home Fire (2017), it considers how this high-profile novel anticipates and negotiates the pressures of anthropological reading practices, including in its representation of the 'veiled' Muslim woman, and highlights the novel's concern with the sensory everyday - especially the aural - as a means of bypassing the violence of surveillance and the visual more broadly in connecting with others. By examining the characters' encounters, the article considers how Home Fire negotiates its implied reader's encounter with the text. It argues that while the novel's success lies partly in its use of spectacular images of Muslims, its overt theatricality in fact opens up a space beyond the frame within which Muslims are normatively seen or read, and enables a reading encounter that resists an easy consumption of difference. Through its analysis of Shamsie's novel, the article explores the possibility of building through reading a 'differentiated solidarity' (Iris Marion Young) - connections forged across lines of difference that nevertheless respect and retain the distinction of that difference - and thereby intervenes in debates about the ethics of writing and reading others.